2005
DOI: 10.1007/s00360-005-0476-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide in the regulation of the systemic and pulmonary vasculature of the rattlesnake, Crotalus durissus terrificus

Abstract: The functional role of nitric oxide (NO) was investigated in the systemic and pulmonary circulations of the South American rattlesnake, Crotalus durissus terrificus. Bolus, intra-arterial injections of the NO donor, sodium nitroprusside (SNP) caused a significant systemic vasodilatation resulting in a reduction in systemic resistance (Rsys). This response was accompanied by a significant decrease in systemic pressure and a rise in systemic blood flow. Pulmonary resistance (Rpul) remained constant while pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
4
19
0
Order By: Relevance
“…This recovery time was four-to fivefold faster than previously observed for a fish, Myoxocephalus scorpius, using similar techniques (Campbell et al, 2004). High fH values, similar to those observed immediately after CO 2 anaesthesia in our study, have been reported for snakes anaesthetised with pentobarbitone (Galli et al, 2005a;Galli et al, 2005b;Skals et al, 2005). In recovered rattlesnakes, equipped with flow probes and/or several vascular catheters, fH has previously been reported to be 25-30·beats·min -1 at 25°C (Skals et al, 2005), whereas values around 20·beats·min .…”
Section: Discussionsupporting
confidence: 87%
“…This recovery time was four-to fivefold faster than previously observed for a fish, Myoxocephalus scorpius, using similar techniques (Campbell et al, 2004). High fH values, similar to those observed immediately after CO 2 anaesthesia in our study, have been reported for snakes anaesthetised with pentobarbitone (Galli et al, 2005a;Galli et al, 2005b;Skals et al, 2005). In recovered rattlesnakes, equipped with flow probes and/or several vascular catheters, fH has previously been reported to be 25-30·beats·min -1 at 25°C (Skals et al, 2005), whereas values around 20·beats·min .…”
Section: Discussionsupporting
confidence: 87%
“…The effect of NO on the venous circulation of reptiles, however, has not been investigated in vivo. In rattlesnakes, SNP decreased P sys , R sys and VS tot as previously shown in this species (Galli et al, 2005a) and caused marked decreases in P CV and MCFP, which indicate that NO has a marked effect on the veins in this species. In trout, injection of SNP had no effect on either P CV or VS and only slightly decreased MCFP (Olson et al, 1997), whereas in toads, SNP caused dilatation of the central veins (Broughton and Donald, 2005).…”
Section: The Effect Of No On the Venous Systemsupporting
confidence: 82%
“…It is well established that SNP reduces systemic resistance in reptiles (Crossley et al, 2000;Galli et al, 2005a;Skovgaard et al, in press) and dilates central veins from Elaphe in vitro (Conklin et al, 1996). The effect of NO on the venous circulation of reptiles, however, has not been investigated in vivo.…”
Section: The Effect Of No On the Venous Systemmentioning
confidence: 99%
“…Many studies in non-mammalian vertebrates (birds, reptiles, amphibians and teleost fishes) have shown that NO mediates vasorelaxation (Olson and Villa, 1991;Knight and Burnstock, 1993;Knight and Burnstock, 1996;Nilsson and Soderstrom, 1997; Martinez-Lemus et al, 1999; Crossley et al, 2000; Axelsson et al, 2001;Broughton and Donald, 2002;Jennings et al, 2004;Broughton and Donald, 2005;Galli et al, 2005;Skovgaard et al, 2005), but there is some controversy as to whether the vascular endothelium synthesises and releases NO in fishes and amphibians. A number of studies have provided evidence that endothelial NO signalling is present in the vasculature of fishes (Mustafa and Agnisola, 1998;Fritsche et al, 2000;Pellegrino et al, 2002) and amphibians (Rumbaut et al, 1995;Knight and Burnstock, 1996).…”
Section: Introductionmentioning
confidence: 99%